Various Structures of 2D Transition‐Metal Dichalcogenides and Their Applications. Issue 11 (29th July 2018) - Wei, Zhongming; Li, Bo; Xia, Congxin; Cui, Yu; He, Jun; Xia, Jian‐Bai; Li, Jingbo
Abstract: 2D transition‐metal dichalcogenides (TMDs), which exhibit fascinating and fantastic properties, have promising applications in future electronic devices and photoelectric devices. Here, the recent research on 2D TMDs is summarized, including single components, 2D doped TMDs, and 2D van der Waals heterostructures. The physical picture, synthetic methods, and optoelectronic properties of these 2D materials are comprehensively described. Opportunities and emerging applications of 2D materials in the future are briefly discussed. Abstract : Recent advances in transition‐metal dichalcogenides, including doping engineering and their heterostructures, are reviewed. The various fabrication strategies for these doped materials and heterostructures, improved electronic and optoelectronic properties after processing, and their applications toward future industrial semiconductor materials are discussed.